2015
DOI: 10.3174/ajnr.a4349
|View full text |Cite
|
Sign up to set email alerts
|

HydroCoils Are Associated with Lower Angiographic Recurrence Rates Than Are Bare Platinum Coils in Treatment of “Difficult-to-Treat” Aneurysms: A Post Hoc Subgroup Analysis of the HELPS Trial

Abstract: BACKGROUND AND PURPOSE:The HydroCoil Endovascular Aneurysm Occlusion and Packing Study was a randomized controlled trial that compared HydroCoils to bare platinum coils. Using data from this trial, we performed a subgroup analysis of angiographic and clinical outcomes of patients with "difficult-to-treat" aneurysms, defined as irregularly shaped and/or having a dome-to-neck ratio of Ͻ1.5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In our study the use of HSC was not associated with an increased incidence of parent vessel perforation, parent vessel occlusion, procedural aneurysm rupture, and thromboembolic events. Further on, recurrence was a high-profile and controversial issue among different clinical trials and systematic reviews: HELPS (Hydrocoil Endovascular aneurysm occlusion and Packing Study), 14 16 GREAT (German--French Randomized Endovascular Aneurysm Trial) 8 , 17 and Serafin's systematic review 18 illustrated that hydrogel coils resulted in a lower rate of recurrence when compared to BPC. In contrast, no significant differences between coil types were observed through Poncyljusz's RCT 19 and PRET (Patients prone to Recurrence after Endovascular Treatment).…”
Section: Discussionmentioning
confidence: 99%
“…In our study the use of HSC was not associated with an increased incidence of parent vessel perforation, parent vessel occlusion, procedural aneurysm rupture, and thromboembolic events. Further on, recurrence was a high-profile and controversial issue among different clinical trials and systematic reviews: HELPS (Hydrocoil Endovascular aneurysm occlusion and Packing Study), 14 16 GREAT (German--French Randomized Endovascular Aneurysm Trial) 8 , 17 and Serafin's systematic review 18 illustrated that hydrogel coils resulted in a lower rate of recurrence when compared to BPC. In contrast, no significant differences between coil types were observed through Poncyljusz's RCT 19 and PRET (Patients prone to Recurrence after Endovascular Treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Some comparative studies of hydrogel-coated coils and inert coils have demonstrated that hydrogel coils achieve greater packing density with decreased coil length and may have lower aneurysm recurrence rates 9 10. Recently published post hoc subgroup analyses of the HydroCoil Endovascular Aneurysm Occlusion and Packing Study (HELPS) demonstrated that, compared with bare platinum coils, the use of HydroCoils is independently associated with significantly lower rates of major recurrence for treatment of ruptured aneurysms <10 mm in size (20% vs 48%) as well as for aneurysms with irregular shapes and wide necks 1 2. However, a recently published meta-analysis showed no statistically significant difference in aneurysm recanalization rates when modified coils such as the HydroCoil were compared with bare platinum coils 11…”
Section: Discussionmentioning
confidence: 99%
“…Ten of the 17 RCT reports (59%) showed a high risk of bias (Figure 2). 35,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] We found improper reporting in 546 of the included studies (40%) (eAppendix 3 in Supplement 1). In 68 studies (5%), the conclusion in the abstract was more positive than the conclusion in the text.…”
Section: Risk Of Biasmentioning
confidence: 99%